Placental teratoma: Unexpected mass following a spontaneous vaginal delivery - Noor Afidah Mohd Shabery; Haza Syakirin Mohamad Zin; Daniel Roza Duski; Azlin Abdul Hadi; Abd Rahman Hayati; Nur Syahrina Rahim (College of Pathologists, Academy of Medicine Malaysia, 2024)
Non-Indexed Publication